Geraniol Suppresses Angiogenesis by Downregulating Vascular Endothelial Growth Factor (VEGF)/VEGFR-2 Signaling - Wittig, Christine; Scheuer, Claudia; Parakenings, Julia; Menger, Michael D.; Laschke, Matthias W. (PloS one, 2015)
Geraniol exerts several direct pharmacological effects on tumor cells and, thus, has been suggested as a promising anti-cancer compound. Because vascularization is a major precondition for tumor growth, we analyzed in this study the anti-angiogenic action of geraniol. In vitro, geraniol reduced the migratory activity of endothelial-like eEND2 cells. Western blot analyses further revealed that geraniol downregulates proliferating cell nuclear antigen (PCNA) and upregulates cleaved caspase-3 (Casp-3) expression in eEND2 cells. Moreover, geraniol blocked vascular endothelial growth factor (VEGF)/VEGFR-2 signal transduction, resulting in a suppression of downstream AKT and ERK signaling pathways. In addition, geraniol significantly reduced vascular sprout formation in a rat aortic ring assay. In vivo, geraniol inhibited the vascularization of CT26 tumors in dorsal skinfold chambers of BALB/c mice, which was associated with a smaller tumor size when compared to vehicle-treated controls. Immunohistochemical analyses confirmed a decreased number of Ki67-positive cells and CD31-positive microvessels with reduced VEGFR-2 expression within geraniol-treated tumors. Taken together, these findings indicate that geraniol targets multiple angiogenic mechanisms and, therefore, is an attractive candidate for the anti-angiogenic treatment of tumors.